Stay Active and Productive in Old Age - Nina Aminah (Health Idea, 2023)
Basically, changes in age affect physical, psychological and social aspects. The elderly's ability to carry out activities has begun to decrease compared to their youth, especially from a physical perspective. Psychological problems that usually arise in old age are feeling useless, feeling lonely, and starting to decline, especially the loss of independence. The emerging problems faced by the elderly require real action to improve their quality of life. What factors influence an elderly person to remain healthy, productive even until they are under or over 100 years old. The aim of this research is how the lives of the elderly remain prosperous both physically and mentally. This research is a type of library research, namely an effort to obtain data based on a library. One of the characteristics of library research is that researchers deal directly with texts or data and not with direct knowledge from the field. The results of this study show that it is recommended that seniors do physical activity for at least 30 minutes at moderate intensity almost every day of the week. Participating in activities such as walking, gardening, doing housework, and going up and down stairs can achieve the desired goals. Physical activities include gardening, daily activities at home, exercise/exercise: walking, low impact aerobics, elderly exercise, cycling, swimming and so on. Social and cultural activities include social organizations, elderly or community organizations, religious activities and continuing to work are healthy. Keywords: active; productive; old age; low impac